PENGARUH EFIKASI DIRI TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS V SDN 25 CAKRANEGARA - Alfian Qori Irsandi; Muhammad Erfan; Hikmah Ramdhani Putri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Mathematics learning outcomes reflect changes that occur in the cognitive, affective, and psychomotor aspects of students after participating in the mathematics learning process, which is influenced by various internal and external factors. One of the internal factors that is thought to play a role in achieving math learning outcomes is self-efficacy. The purpose of this study was to determine the extent of the influence of self-efficacy on the mathematics learning outcomes of grade V students at SDN 25 Cakranegara in the 2024/2025 school year. This study used a quantitative approach with a correlational method. The research subjects consisted of 22 fifth grade students of SDN 25 Cakranegara. Data collection was done through a self-efficacy questionnaire and a math learning outcomes test. Data analysis used regression techniques as a form of inferential analysis. The results showed that there was a significant influence between self-efficacy on the mathematics learning outcomes of fifth grade students of SDN 25 Cakranegara with the acquisition of t_hitung 5.279 > 2.086 t_table. Self-efficacy contributes 58.2% to math learning outcomes, which is classified in the moderate category. Based on the results obtained, it can be concluded that H_0 is rejected and H_a is accepted, which means that there is an influence between self-efficacy on the mathematics learning outcomes of fifth grade students of SDN 25 Cakranegara in the 2024/2025 school year.